Study of The Generalized Bose-Einstein Condensation in Various Dimensions Based on Fractional Quantum Mechanics - Bouzenna, Fatma El-Ghenbazia (University of Eloued جامعة الوادي, 2020)
In this thesis, we study the effect of fractional derivative on Bose-Einstein condensation. Firstly, we consider Caputo-Fabrizio derivative of order α (1 < α ≤ 2) to derive the eigenvalues of fractional Schrodinger equation for a free particle in a 3-dimensional box [0, L]. Afterwards, we consider 3D Bose-Einstein condensation of an ideal gas with the obtained energy spectrum. Interestingly, the critical temperatures of condensation Tc for α ≠ 2 are greater than the standard one. Furthermore, the condensation in 2D is shown to be possible. The thesis also treats the time-independent one-dimensional fractional Schr¨odinger equation. At first stage, by using Caputo-Fabrizio definition and other own results, we have transformed the fractional Schrodinger equation to an ordinary linear differential equation. Secondly, we have applied the last result to solve two problems in fractional quantum mechanics: the Coulomb-type and Hulthen-type potentials in one dimension. The eigenenergy and eigenfunction are calculated. Moreover, we solve time, space, and space-time fractional Schr¨odinger equations based on the same derivative definition for 1D infinite-potential well problem. To reach this goal, we first work out the fractional differential equations defined in terms of Caputo-Fabrizio derivative. Hence, the eigenvalues and the eigenfunctions of the three kinds of fractional Schrodinger equations are derived. It turns out that, unlike the Laskin results which are based on the Riesz derivative, we found that the wave number and the wave function are different from the standard case. Moreover, the number of solutions is finite and depends on the space derivative order. In the limiting case, for α = 2, our results are in complete agreement with those presented in standard quantum physics and statistical mechanics. ندرس في هذه الرسالة تأثير المشتق الكسري على تكثف بوز-آينشتاين. حيث قمنا أولا بحل معادلة شرودينغر الكسرية لجسيم حر محصور في علبة ثلاثية الأبعاد وذلك بالاعتماد على تعريف كابيتو-فابريزيو للاشتقاق الكسري ذو الرتبةα . (1< α ≤ 2) . بعدها ، تمت دراسة تكثف بوز-آينشتاين ثلاثي البعد لغاز مثالي معرّف بطيف الطاقة المتحصل عليه سابقا. ومن المثير للاهتمام أنه في هذا الغاز، تكون درجة الحرارة الحرجة Tc عند α ≠ 2 أعلى من درجة الحرارة الحرجة العادية. كما قمنا باثبات امكانية التكثف في بعدين لهذا الغاز. تعالج الأطروحة أيضًا بعض المسائل في ميكانيك الكم الكسري باستخدام تعريف كابيتو-فابريزيو. فمن خلال تحويل معادلة شرودنغر الكسرية المستقلة عن الزمن إلى معادلة تفاضلية خطية عادية قمنا باشتقاق الطاقة الذاتية ودالة الموجة الموافقة لمسألتي كولوم وهيلثون. بالإضافة إلى ذلك ، تطرقنا لحل مسألة البئر الكموني اللانهائي لثلاثة أنواع من معادلات شرودينغر: - ذات المشتق الزمني الكسري - ذات المشتق المكاني الكسري - معادلة شرودينغر الكسرية المعمّمة ذات المشتقين الزمني والمكاني الكسريين. بالاعتماد على نفس المشتق الكسري تم اشتقاق القيم الذاتية والدوال الذاتية للمعادلات الثلاثة. على عكس نتائج لاسكين التي تستند إلى مشتق ريتز، عبارة كل من العدد الموجي ودالة الموجة الناتجة مختلفة تماما عن الحالة العادية. علاوة على ذلك ، فإن عدد الحلول محدود ويعتمد على رتبة المشتق المكاني. عند α = 2 تتوافق نتائجنا تمامًا مع نتائج ميكانيك الكم العادي وميكانيك الإحصاء.
Thesis presented to obtain the degree of Doctorate LMD Specialty Radiation, matter and energy
Keywords: Fractional derivative, Bose-Einstein condensation, Caputo-Fabrizio derivative, Fractional Shcrodinger equation, Critical temperatures.; المشتق الكسري ، تكثف بوز-آينشتاين ، مشتق كابوتو-فابريزيو ، معادلة شرودنغر الكسرية ، درجات الحرارة الحرجة.